Profile of Muscle Strength and Physical Performance with the Incidence of Urinary Incontinence in Elderly Women - Jihan Nabila Pranjasdhina; Novira Widajanti; Rwahita Satyawati Dharmanta (Humanistic Network for Science and Technology (HNST), 2021)
Introduction: The 200 million people in the world experience urinary incontinence. In general, with increasing age, the capacity of the bladder decreases. The remaining urine in the bladder tends to increase and irregular contraction of the bladder muscles becomes more frequent. This situation often makes the elderly experience problems with the fulfillment of urine elimination needs, namely urinary incontinence. Efforts to overcome urinary incontinence in the form of bladder training programs are aimed at developing muscle tone and bladder sphincter so that it can function optimally. Objective: Knowing the profile of muscle strength and physical performance with the incidence of urinary incontinence in elderly women. Methods: This research was a retrospective descriptive study based on the results of filling out the questionnaire and evaluating it directly. Based on tabulated data, 38 elderly women were selected as the study sample. Results: There were (42.1%) urinary incontinence on elderly with very poor left hand muscle strength and (50%) urinary incontinence on elderly with very poor right hand muscle strength. In physical performance with urinary incontinence as many as (57.8%) were normal and (42.1%) were poor. Conclusions: Muscle strength and physical performance can be used as a measurement to early detection of the urinary incontinence. Keywords: urinary incontinence; muscle strength; physical performance; descriptive retrospective study